Belostoma martini (Montandon): description of the instars and redescription of the adult (Hemiptera: Belostomatidae) - Estévez, Ana L.; Schnack, Juan A. (Zootaxa, 2007)
The five instars, and the adult of Belostoma martini (Montandon) are described and redescribed, respectively. All stages of development were captured at “Arroyo La Tapera”, Mar del Plata, Buenos Aires Province, Argentina (30o 00’S, 57o 33’ W). In addition, the instars of the eight Belostoma species from Argentina whose immatures are known, including B. martini, are compared.